2009
DOI: 10.4103/0019-5359.53164
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor (FokI, BsmI and TaqI) gene polymorphisms and type 2 diabetes mellitus : A North Indian study

Abstract: BACKGROUND:The vitamin D receptor (VDR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 38 publications
5
48
0
Order By: Relevance
“…Simultaneous companion of autoimmune diseases and diabetes may double the risk of osteoporosis in these patients (10). In addition to influencing the pathophysiology on bone diseases caused by diabetes, bone density disorder in type 1 DM is also influenced by genetic factors (11). Also, increasing risk of fractures has been reported in diabetic patients treated with insulin drugs than non-insulin drugs (12).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous companion of autoimmune diseases and diabetes may double the risk of osteoporosis in these patients (10). In addition to influencing the pathophysiology on bone diseases caused by diabetes, bone density disorder in type 1 DM is also influenced by genetic factors (11). Also, increasing risk of fractures has been reported in diabetic patients treated with insulin drugs than non-insulin drugs (12).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Asian population by Li et al (2013), suggested that there might be a correlation between polymorphisms at the FokI site and onset of T2DM. A study in North Indian population conducted by Bid et al (2009), was aimed at analyzing association between polymorphisms of VDR gene and genetic predisposition to T2DM. They evaluated SNPs of FokI (T/C) [rs2228570], BsmI (A/G) [rs1544410] and TaqI (C/T) [rs731236] using PCR-RFLP technique similar to this study, but did not find any significant association between the polymorphisms at any of the sites studied between patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting glucose was measured photometrically according to the manufacture's instructions using the Dimension Vista ® System (Siemens AG, Erlangen, Germany). Vitamin D Total (VitD) was measured by ADVIA Centaur ®immunoassay System (Siemens, USA) (Bid et al, 2009). …”
Section: Blood Biochemistry Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this result, the present study clearly indicates a role of the recessive t allele in development of GDM. Bid et al (2009) performed a study on the same sites on an Indian population and did not report any association between the VDR gene polymorphism and type II diabetes. The fact that there are discrepancies between various studies could be attributed to the variation in gene pool among various ethnic groups in the VDR gene loci.…”
Section: Discussionmentioning
confidence: 99%